2020
DOI: 10.1002/jbmr.4502
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary IFT88 Protects Coordinated Adolescent Growth Plate Ossification From Disruptive Physiological Mechanical Forces

Abstract: Compared with our understanding of endochondral ossification, much less is known about the coordinated arrest of growth defined by the narrowing and fusion of the cartilaginous growth plate. Throughout the musculoskeletal system, appropriate cell and tissue responses to mechanical force delineate morphogenesis and ensure lifelong health. It remains unclear how mechanical cues are integrated into many biological programs, including those coordinating the ossification of the adolescent growth plate at the cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Mechanical loading also stimulates the formation of a secondary ossification center, protecting the hypertrophic chondrocytes in the growth plate from potential injury due to high mechanical stress [ 8 ]. In addition to the protection from bone tissue, the growth-plate chondrocytes resist mechanical injuries through several mechanisms, such as inducing autophagy [ 15 ] and extension of the primary cilium [ 16 , 17 ]. For example, ciliary gene intraflagellar transport protein 88 (Ift88) knock-out (KO) mice showed narrow growth plate and endochondral ossification inhibition [ 16 ], demonstrating that Ift88 helped promote chondrocyte ciliation, cartilage resorption, mineralization, and, finally, coordinated ossification of growth plate from the disruptive mechanical force.…”
Section: Overview Of the Factors Maintaining The Growth Platementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical loading also stimulates the formation of a secondary ossification center, protecting the hypertrophic chondrocytes in the growth plate from potential injury due to high mechanical stress [ 8 ]. In addition to the protection from bone tissue, the growth-plate chondrocytes resist mechanical injuries through several mechanisms, such as inducing autophagy [ 15 ] and extension of the primary cilium [ 16 , 17 ]. For example, ciliary gene intraflagellar transport protein 88 (Ift88) knock-out (KO) mice showed narrow growth plate and endochondral ossification inhibition [ 16 ], demonstrating that Ift88 helped promote chondrocyte ciliation, cartilage resorption, mineralization, and, finally, coordinated ossification of growth plate from the disruptive mechanical force.…”
Section: Overview Of the Factors Maintaining The Growth Platementioning
confidence: 99%
“…In addition to the protection from bone tissue, the growth-plate chondrocytes resist mechanical injuries through several mechanisms, such as inducing autophagy [ 15 ] and extension of the primary cilium [ 16 , 17 ]. For example, ciliary gene intraflagellar transport protein 88 (Ift88) knock-out (KO) mice showed narrow growth plate and endochondral ossification inhibition [ 16 ], demonstrating that Ift88 helped promote chondrocyte ciliation, cartilage resorption, mineralization, and, finally, coordinated ossification of growth plate from the disruptive mechanical force. Additionally, the Sprouty family, a modulator of the receptor tyrosine kinase signaling pathway, maintains the morphology of the primary cilium of chondrocytes in the growth plate [ 17 ].…”
Section: Overview Of the Factors Maintaining The Growth Platementioning
confidence: 99%
“…Several ciliopathies are associated with liver diseases, including biliary fibrosis (Mansini et al, 2018). Intraflagellar transport 88 (IFT88), a component of the IFT system, is vital for cilium formation and maintenance (Coveney, Samvelyan, et al, 2022; W. Li et al, 2022; Y. Yang et al, 2021). Mutations or disruptions in IFT88 have been implicated in cilia dysfunction, leading to the development of ciliopathies, including polycystic liver and kidney disease (Coveney, Zhu, et al, 2022; R. Fujii et al, 2021; Shao et al, 2020; Y. Wu et al, 2023; S. Yang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Coveney and colleagues ( 9 ) in this issue of JBMR goes on to describe an unexpected function for primary cilia in cartilage. Based on the known role of primary cilia in other cell types, it was presumed that primary cilia would be required to transmit mechanical signals in chondrocytes; however, evidence for a positive role for primary cilia in propagating mechanical signals in cartilage in vivo had been elusive.…”
mentioning
confidence: 99%
“…In this issue of JBMR, two studies address broad questions about cartilage patterning and the role of primary cilia in coordinating chemical and mechanical signals. (8,9) Rux and colleagues (8) generated mice with a conditional deletion of Ift88 in joint progenitor cells via Gdf5-expressed Cre. They observed that subsequent reduction in primary cilia resulted in disruptions to the organization and localization of the tidemark in articular cartilage in a way that was dependent on the type of load experienced by the cartilage.…”
mentioning
confidence: 99%